Pregnancy during a Pandemic: A Cohort Study Comparing Adverse Outcomes during and before the COVID-19 Pandemic - Rao, Manasa G.; Toner, Lorraine E.; Stone, Joanne; Iwelumo, Chioma A.; Goldberger, Cody; Roser, Brittany J.; Shah, Ruhee; Rattner, Paige; Paul, Keisha S.; Stoffels, Guillaume; Bianco, Angela (American Journal of Perinatology, 2022)
Objective This study was aimed to evaluate how the novel coronavirus disease 2019 (COVID-19) pandemic may have negatively impacted birth outcomes in patients who tested negative for the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) virus.Study Design We conducted a retrospective cohort study using electronic health records of pregnant women admitted to a tertiary medical center in New York City, an epicenter of the pandemic. Women with a singleton gestation admitted for delivery from March 27 to May 31, 2019, and March 27 to May 31, 2020, were included. Women less than 18 years of age, those with a positive SARS-CoV-2 polymerize chain reaction (PCR) test on admission, fetal anomaly, or multiple gestation were excluded. Adverse pregnancy outcomes were compared between groups. Univariable and multivariable logistic regression analyses were used to assess outcomes. The primary outcome was preterm birth.Results Women who delivered during the 2020 study interval had a significantly higher rate of hypertensive disorders of pregnancy (gestational hypertension [GHTN] or preeclampsia; odds ratio [OR] = 1.40, 95% confidence interval [CI]: 1.05–1.85; p = 0.02), postpartum hemorrhage (PPH; OR = 1.77, 95% CI: 1.14–2.73; p = 0.01), and preterm birth (OR = 1.49, 95% CI: 1.10–2.02; p = 0.01). Gestational age at delivery was significantly lower in the 2020 cohort compared with the 2019 cohort (39.3 versus 39.4 weeks, p = 0.03). After adjusting for confounding variables, multivariate analysis confirmed a persistent increase in hypertensive disorders of pregnancy (OR = 1.56, 95% CI: 1.10–2.20, p = 0.01), PPH (OR = 1.74, 95% CI: 1.06–2.86, p = 0.03), and preterm birth (OR = 1.72, 95% CI: 1.20–2.47, p = 0.003) in patients who delivered in 2020 compared with the same period in 2019. Specifically, medically indicated preterm births increased during the pandemic (OR = 3.17, 95% CI: 1.77–5.67, p < 0.0001).Conclusion Those who delivered during the COVID-19 pandemic study interval were more likely to experience hypertensive disorders of pregnancy, medically indicated preterm birth, and PPH even in the absence of SARS-CoV2 infection.Key Points
Keywords: pregnancy; COVID-19; preterm birth; pandemic stress; postpartum hemorrhage; gestational hypertension; preeclampsia; hypertensive disorders of pregnancy